2015
DOI: 10.1186/s12913-015-0762-y
|View full text |Cite
|
Sign up to set email alerts
|

Ghana’s National Health insurance scheme and maternal and child health: a mixed methods study

Abstract: BackgroundGhana is attracting global attention for efforts to provide health insurance to all citizens through the National Health Insurance Scheme (NHIS). With the program’s strong emphasis on maternal and child health, an expectation of the program is that members will have increased use of relevant services.MethodsThis paper uses qualitative and quantitative data from a baseline assessment for the Maternal and Newborn errals Evaluation from the Northern and Central Regions to describe women’s experiences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 29 publications
5
66
0
1
Order By: Relevance
“…While our current analysis cannot address the reasons for non-enrollment, other analysis shows that convenience and perceived benefits of health insurance can sway women to enroll in the NHIS within certain regions of Ghana [33]. Other qualitative data point out that poverty and “uncertainties” around being referred to facilities (transport, costs, dealing with a new facility) as barriers to facility care [29]. Further work to understand the non-enrollment of women in the NHIS can be undertaken to broader the evidence base on this area.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While our current analysis cannot address the reasons for non-enrollment, other analysis shows that convenience and perceived benefits of health insurance can sway women to enroll in the NHIS within certain regions of Ghana [33]. Other qualitative data point out that poverty and “uncertainties” around being referred to facilities (transport, costs, dealing with a new facility) as barriers to facility care [29]. Further work to understand the non-enrollment of women in the NHIS can be undertaken to broader the evidence base on this area.…”
Section: Discussionmentioning
confidence: 98%
“…We also note that nearly all women have been to ANC at least once [30] and close to 9 out of 10 have had at least four ANC visits though SBA use is much lower suggesting that the barriers to SBA are different to those of ANC. A sub-national study in Ghana points out that ANC visits incur less indirect costs as women can usually walk to ANC visits though this is not possible immediately before birth [29], while other studies in Nepal and rural Kenya show that distance and accessibility to a facility for maternity care are key barriers to SBA use [3940]. The disparity between ANC use and SBA use also may indicate the need to implement or strengthen counseling on birth preparedness plans for pregnant women which addresses the “three delays” for maternal care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghana instituted its National Health Insurance Scheme (NHIS) in 2003 -with a primary objective to limit cost as a barrier to accessing MNCH services. A recent study in northern Ghana illustrated that enrolment in the NHIS had a positive association with uptake of institutional delivery; however, there was no effect on women's attendance of four or more ANC visits (Singh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ghana instituted its National Health Insurance Scheme (NHIS) in 2003 -with a primary objective to limit cost as a barrier to accessing MNCH services. A recent study in northern Ghana illustrated that enrolment in the NHIS had a positive association with uptake of institutional delivery; however, there was no effect on women's attendance of four or more ANC visits (Singh et al 2015).Socio-cultural factors have also been shown to be important determinants of MNCH behaviours in SSA, including ANC attendance (Ahmed et al 2010;Hiarlaithe et al 2014;Pell et al 2013;Simkhada et al 2008;Underwood et al 2014). A study on facility delivery in northern Ghana, for example, found that traditional power hierarchies in the household and communities influenced the uptake of key health-seeking behaviours, and that often "someone must give the order", potentially hindering uptake of essential MNCH behaviours (Moyer et al 2014).…”
mentioning
confidence: 99%